Hubungan Pengaruh Internet Dan Lingkungan Sekolah Terhadap Gaya Berbahasa Siswa - Afrilia Disa Pravinta; Atim Subekti; Muhamad Yahya (Arsy : Jurnal Studi Islam, 2022)
This study aims to determine and analyze the influence of the internet and the school environment on the language style of students in Class VII MTsN 16 Jombang. The method used in this research is a quantitative approach. The population data used in this study is student data in the 2019-2020 school year. Where there are about a total of 73 students of class VII. The total population in each class VII of MTsN 16 Tembelang Jombang has been 100% sampled, so that the total sample used by the researcher is 73 students, who were selected as a whole in each class. Based on the research that has been done, it can be concluded that the influence of the Internet and the Environment is in the high category as many as 16 respondents or equivalent to 22 percent, in the medium category as many as 31 respondents or equivalent to 42 percent and in the low category as many as 27 respondents or equivalent to 36 percent. Thus, most of the respondents, namely 31 respondents, chose Internet and Environment to be in the moderate or good enough category